Cardiac fibroblasts : Active players in (atrial) electrophysiology? - Klesen,A; Jakob,D; Emig,R; Kohl,P; Ravens,U; Peyronnet,R (Herzschrittmacherther Elektrophysiol, 2018)
Fibrotic areas in cardiac muscle-be it in ventricular or atrial tissue-are considered as obstacles for conduction of the excitatory wave and can therefore facilitate re-entry, which may contribute to the sustenance of cardiac arrhythmias. Persistence of one of the most frequent arrhythmias, atrial fibrillation (AF), is accompanied by enhanced atrial fibrosis. Any kind of myocardial perturbation, whether via mechanical stress or ischemic damage, inflammation, or irregular and high-frequency electrical activity, activates fibroblasts. This leads to the secretion of paracrine factors and extracellular matrix proteins, especially collagen, and to the differentiation of fibroblasts into myofibroblasts. Excessive collagen production is the hallmark of fibrosis and impairs regular impulse propagation. In addition, direct electrical coupling between cardiomyocytes and nonmyocytes, such as fibroblasts and macrophages, via gap junctions affects conduction. Although fibroblasts are not electrically excitable, they express functional ion channels, in particular K+ channels and mechanosensitive channels, some of which could be involved in tissue remodeling. Here, we briefly review these aspects with special reference to AF.